Panel of New Thermostable CYP116B Self‐Sufficient Cytochrome P450 Monooxygenases that Catalyze C−H Activation with a Diverse Substrate Scope. Issue 5 (8th January 2018) - Tavanti, Michele; Porter, Joanne L.; Sabatini, Selina; Turner, Nicholas J.; Flitsch, Sabine L.
Abstract: The ability of cytochrome P450 monooxygenases to catalyse a wide variety of synthetically challenging C−H activation reactions makes them highly desirable biocatalysts both for the synthesis of chiral intermediates and for late‐stage functionalisations. However, P450s are plagued by issues associated with poor expression, solubility and stability. Catalytically self‐sufficient P450s, in which the haem and reductase domains are fused in a single protein, obviate the need for additional redox partners and are attractive as biocatalysts. Here we present a panel of natural self‐sufficient P450s from thermophilic organisms (CYP116B65 from A. thermoflava, CYP116B64 from A. xiamenense, CYP116B63 from J. thermophila, CYP116B29 from T. bispora and CYP116B46 from T. thermophilus ). These P450s display enhanced expression and stability over their mesophilic homologues. Activity profiling of these enzymes revealed that each P450 displayed a different fingerprint in terms of substrate range and reactivity that cover reactions as diverse as hydroxylation, demethylation, epoxidation and sulfoxidation. The productivity of the bio‐transformation of diclofenac to produce the 5‐hydroxy metabolite increased 42‐fold using the thermostable P450‐AX (>0.5 g L −1  h −1 ) compared to the P450‐RhF system reported previously. In conclusion, we have generated a toolkit of thermostable self‐sufficient P450 biocatalysts with a broad substrate range and reactivity. Abstract : Looking to nature : P450s are often limited by poor expression, stability, and efficiency. The use of catalytically self‐sufficient P450s from thermophilic organisms combines naturally evolved stability and efficiency conveniently to yield biocatalysts suitable for further engineering and industrial application.